Equity of access to maternal health interventions in Brazil and Colombia: a retrospective study - Amaila De La Torre; Zlatko Nikoloski; Elias Mossialos (BMC, 2018)
Abstract Background Reducing maternal mortality is a top priority in Latin American countries. Despite the progress in maternal mortality reduction, Brazil and Colombia still lag behind countries at similar levels of development. Methods Using data from the Demographic Health Survey, this study quantified and compared, by means of concentration indices, the socioeconomic-related inequity in access to four key maternal health interventions in Brazil and Colombia. Decomposition analysis of the concentration index was used for two indicators - skilled attendance at birth and postnatal care in Brazil. Results Coverage levels of the four key maternal health interventions were similar in the two countries. More specifically, we found that coverage of some of the interventions (e.g. ante-natal care and skilled birth assistance) was higher than 90% in both countries. Nevertheless, the concentration index analysis pointed to significant pro-rich inequities in access in all four key interventions in both countries. Interestingly, the analysis showed that Colombia fared slightly better than Brazil in terms of equity in access of the interventions studied. Finally, the decomposition analysis for the presence of a skilled attendant at birth and postnatal care in Brazil underlined the significance of regional disparities, wealth inequalities, inequalities in access to private hospitals, and inequalities in access to private health insurance. Conclusions There are persistent pro-rich inequities in access to four maternal health interventions in both Brazil and Colombia. The decomposition analysis conducted on Brazilian data suggests the existence of disparities in system capacity and quality of care between the private and the public health services, resulting in inequities of access to maternal health services.